2014
DOI: 10.12703/p6-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding pituitary tumors

Abstract: Pituitary tumors are common in the general population. Since neuroimaging techniques have improved, pituitary tumors are more often diagnosed incidentally. About 16.7% of the general population show changes in the pituitary gland. Predominantly, pituitary tumors are benign pituitary adenomas. Pituitary carcinomas or aggressive pituitary tumors are extremely rare. They might develop from benign adenomas. New genetic and epigenetic abnormalities help us to understand pituitary tumorigenesis and might lead to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 48 publications
1
35
0
2
Order By: Relevance
“…Vidal et al limited [36][37][38]. In our study, these tumors showed the highest values of Topo2A expression and a high recurrence rate.…”
Section: Discussionsupporting
confidence: 49%
“…Vidal et al limited [36][37][38]. In our study, these tumors showed the highest values of Topo2A expression and a high recurrence rate.…”
Section: Discussionsupporting
confidence: 49%
“…The possibility exists to introduce agents inhibiting the expression of topo IIα in hormone immunonegative adenomas where pharmacotherapy is currently limited. [37][38][39] In our study, these tumors showed the highest topo IIα expression levels and a high recurrence rate.…”
mentioning
confidence: 80%
“…Elevated levels of cytokines alter the physiological hormone production to adapt the R245 Review m sapochnik and others IL-6 and pituitary senescence endocrine system to the needs of the organism to respond adequately to pathogens. Pituitary tumors are mostly benign, non-metastatic and monoclonal neoplasms constituted by cells of the adeno-pituitary gland, which generally cause small lesions and present a slow growth (Scheithauer et al 2006, Dworakowska & Grossman 2009, Melmed 2011, 2015, Lake et al 2013, Kopczak et al 2014. The pathophysiological consequences of a pituitary adenoma are related to overproduction of particular pituitary hormones or due to tumor compression and damage to the normal pituitary and vital structures surrounding it (Yu & Melmed 2010).…”
Section: Pathophysiological Role Of Il-6 In the Pituitarymentioning
confidence: 99%